Peran Orangtua Di Homeschooling Primagama Palembang - Hidayati Hidayati (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2018)
This research was conducted in Primagama Homeschooling Palembang. The purpose of this research was to analyze the role of parents in Primagama Homeschooling Palembang. Research was conducted using a qualitative approach. In obtaining data, this research used interview techniques to three respondents, namely parents of Primagama Homeschooling Palembang students. The results showed that homeschooling parents acted as facilitators that facilitated children's educational needs in three processes, namely (1) the planning process, in which parents played a role in coordinating with the Primagama Homeschooling Institute regarding children's difficulties in learning. Then parents together with the HSPG determine learning approaches and methods that are appropriate to the child's abilities; (2) the implementation process, in which parents play a role in conducting study assistance at home and accompanying several activities held by Primagama Homeschooling Palembang which involve the role of parents in it; and (3) evaluation process, in which parents play a role in monitoring the development of children's learning outcomes through reports on learning outcomes and further coordinating in determining the learning process that suits the needs of the child.Â